Relationship Between Cost Efficiency and Stock Price: Evidence from Bangladeshi Commercial Banks - Gupta, Chinmoy Das (International Finance and Banking, 2024)
This paper employs Stochastic Frontier Approach (SFA) and Data Envelopment Analysis (DEA) to measure cost efficiency score of 30 listed private commercial banks in Dhaka Stock Exchange (DSE) and finds its influence on stock prices. Results suggest that, there is a significant impact of changes in share prices on the cost efficiency score. This suggests, those banks are most cost efficient, they are able to generate more return for their stockholder than those of inefficient banks.